Analysis Of Additional Value At Pabrik Gula Kwala Madu PTPN II - Muhammad Thamrin; Desi Novita; Dita Ananda Sari (JASc (Journal of Agribusiness Sciences), 2018)
This research was conducted at Pabrik Gula Kwala Madu PT. Perkebunan Nusantara II in Desa Kwala Begumit, Kecamatan Stabat, Kabupaten Langkat. The purpose of this research is to know the development of production and productivity of cane and sugar, to know the added value from cane processing to sugar. The research method used is survey method, with the sample of this research is staff processing section and staff section of production, sample determination is done by purposive sampling. The first used analysis method is trend analysis to know the development of cane and sugar production, the second using hayami method for value-added analysis. The results of this study show that the development of caneand sugar  production and productivity at Pabrik Gula Kwala Madu PTPN II from 2007-2017 always fluctuated. The increase and decrease of production is not fixed every year. The result of value added analysis of sugarcane by using hayami method showed that the added value of cane to sugar obtained is positive because the value added ratio> 0% is equal to 75%.